Self-reported dual sensory impairment and related factors: a European population-based cross-sectional survey - Leveziel, Nicolas; Marillet, Simon; Braithwaite, Tasanee; Peto, Tunde; Ingrand, Pierre; Pardhan, Shahina; Bron, Alain M.; Jonas, Jost B.; Resnikoff, Serge; Anne, Little Julie; Davis, Adrian C.; McMahon, Catherine M.; et al. (British journal of ophthalmology, 2023)
Background Data on population-based self-reported dual vision and hearing impairment are sparse in Europe. We aimed to investigate self-reported dual sensory impairment (DSI) in European population. - Methods A standardised questionnaire was used to collect medical and socio-economic data among individuals aged 15 years or more in 29 European countries. Individuals living in collective households or in institutions were excluded from the survey. - Results Among 296 677 individuals, the survey included 153 866 respondents aged 50 years old or more. The crude prevalence of DSI was of 7.54% (7.36-7.72). Among individuals aged 60 or more, 9.23% of men and 10.94% of women had DSI. Eastern and southern countries had a higher prevalence of DSI. Multivariable analyses showed that social isolation and poor self-rated health status were associated with DSI with ORs of 2.01 (1.77-2.29) and 2.33 (2.15-2.52), while higher income was associated with lower risk of DSI (OR of 0.83 (0.78-0.89). Considering country-level socioeconomic factors, Human Development Index explained almost 38% of the variance of age-adjusted prevalence of DSI. - Conclusion There are important differences in terms of prevalence of DSI in Europe, depending on socioeconomic and medical factors. Prevention of DSI does represent an important challenge for maintaining quality of life in elderly population.